MEWUJUDKAN POTENSI LOKAL TANAMAN JAGUNG UNTUK WARGA DESA MELALUI KULIAH (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
This paper aims to find out the local potential in Tebuwung Village. The author, together with the entrepreneurship division, numbered thirteen people conducted three times surveys and observations in Tebuwung Village in the context of implementing a community service program. The results of the survey can be used as data and materials to mapping problems and find useful solutions for Tebuwung Village. The method used in this writing is descriptive qualitative. While the method of implementing activities is the provision of material and practice with the subject. The results obtained from this activity were that the subjects had never carried out a simulation or practice using corn hair base material. The subjects have also never marketed corn hair into a product that has a high selling value. It is expected that in the subsequent service activities, a sustainable agenda can be implemented using the same products with a wider marketing scope.